2019
DOI: 10.1088/1742-6596/1235/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Smart Travel System For Support Travel And Accommodation Industry

Abstract: Smart Travel System that called To-Tour is an important component in Travelling and Accommodation Services. There are variety and different organization for support the integration mechanism. We proposed the concept of implementation about travel reservation solution that called To-Tour for use by travellers using on Service Oriented Analysis and Design Approach, specifically in Service Oriented Architecture (SOA). To-Tour is a Tour Travel Agency offering any trips from different vendor, and provide any variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Moreover, there is little difference in the opinions of different genders, types of systems, and different frequencies within their results. Therefore, the results of the study have found that most people's feelings of tourism satisfaction are not consistent, which is inconsistent with the literature [41,42]. Therefore, the research hypotheses 1-3 are not valid.…”
Section: Tourism Satisfactioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Moreover, there is little difference in the opinions of different genders, types of systems, and different frequencies within their results. Therefore, the results of the study have found that most people's feelings of tourism satisfaction are not consistent, which is inconsistent with the literature [41,42]. Therefore, the research hypotheses 1-3 are not valid.…”
Section: Tourism Satisfactioncontrasting
confidence: 69%
“…Various countries have used cloud technology in the leisure, tourism industry, and activities for many years. The development and application of the current intelligent transportation system [41] and the effect of linking software systems with the development of related industries have had many years of successful experience [42]. China has tapped a large number of foreign high-tech talents, cultivated domestic manpower, and borrowed the country's scientific and technological experience, and the technology and technology of domestic urban smart transportation systems have gradually become stable and mature.…”
Section: Tourism Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation